Hubungan Pendidikan dan Umur Ibu Hamil Dengan Kelengkapan Pemeriksaan Kehamilan (K4) - Evi Cahya Wulandari; Rita Ariesta (Akademi Kebidanan La Tansa Mashiro, 2014)
The purpose of this study to obtain information about the relationship characteristics of pregnant women with antenatal completeness (K4). The method used in this research is analytic survey with cross sectional design. Made to all mothers who have babies in the village Sangkanmanik of 60 people. These results indicate that the scope of K4 has not reached the target (68.3%). The results showed that antenatal visit is not complete more on education ≤ SLTP 27 (81.8%), mothers aged 20-35 years 32 (65.3%), parity ≥ 2 28 (65.1%). The results of the statistical test showed that there was a significant relationship between maternal education with complete prenatal care while age and parity no significant relationship with completeness antenatal (K4) in the Village District of Cimarga Sangkanmanik 2011. The need for improvement of better health care at the health center or especially qualified midwives in order to improve public health.